Oxygen group-containing activated carbon aerogel as an electrode material for supercapacitor. (October 2015) - Lee, Eo Jin; Lee, Yoon Jae; Kim, Jeong Kwon; Lee, Minzae; Yi, Jongheop; Yoon, Jung Rag; Song, Jae Chun; Song, In Kyu
Graphical abstract: Highlights: Activated carbon aerogel (ACA) was prepared by activating carbon aerogel with CO2 . Modified ACAs (MACA- X, X = 3, 6, 9, and 12 h) were prepared by HNO3 oxidation of ACA. MACA-6 h showed the best rate capability and the highest specific capacitance. An optimal condition was required for the highest supercapacitive performance. Abstract: Carbon aerogel was prepared by a sol–gel polymerization of resorcinol–formaldehyde (RF) method, and it was activated with CO2 to obtain activated carbon aerogel (ACA). A series of modified activated carbon aerogels (MACA- X, X = 3, 6, 9, and 12 h) were then prepared by HNO3 oxidation of ACA with a variation of oxidation time ( X ) in order to investigate the effect of surface oxygen group on their electrochemical performance as supercapacitor electrode material. Electrochemical properties of ACA and MACA- X were measured by cyclic voltammetry, galvanostatic charge/discharge, and EIS (electrochemical impedance spectroscopy) measurements. Among the samples, MACA-6 h showed the best rate capability and the highest specific capacitance. Thus, an optimal HNO3 oxidation condition was required for the highest supercapacitive electrochemical performance of modified activated carbon aerogel.